Assessment of the Exposure of People to Questing Ticks Carrying Agents of Zoonoses in Aosta Valley, Italy - Millet, Ilary (Vet Sci, 2019)
We estimated the probability of exposure of people to questing ticks, infected with bacterial agents of the tick—borne zoonoses—in Aosta Valley, western Alps, Italy. We collected ticks by dragging, and from collectors’ clothes in three hiking trails, which were divided into an internal path, with short vegetation, and an external part with taller grass. Dragging yielded 285 Ixodes ricinus nymphs and 31 adults, and two Dermacentor marginatus adults. Eleven I. ricinus nymphs and 9 adults were collected from collectors’ clothes. Borrelia burgdorferi s.l. was identified by PCR in 12 out of 30 I. ricinus nymphs (prevalence = 40.0%, 95% confidence interval = 22.5, 57.5). The prevalence of infection by Rickettsia spp. was 13.3% (95% CI = 1.2, 25.5). The probability of encountering at least one questing I. ricinus infected by each bacterial agent (probability of exposure, E) in 100 m(2) was obtained by combining the number of collected nymphs, the prevalence of infection by each bacterial agent, the frequency of passage by visitors, and the probability of tick attachment to people. The mean number of nymphs collected by dragging was greatest in the internal part of hiking trails (mean = 7.9). Conversely, E was greater in the external part (up to 0.14 for B. burgdorferi s.l., and 0.07 for Rickettsia spp.), due to a greater probability of tick attachment to people in relatively tall vegetation.